Graphene and Its Derivatives Synthesis and Applications - Ahmad, Ishaq; Ezema, Fabian I. (IntechOpen, 2019)
Graphene and its derivatives are potential nanomaterials currently being widely investigated for diverse applications due to its exceptional mechanical, electrical, physical, and chemical properties. Examples of the applications include drug delivery, shape memory polymers, gene delivery, biosensor, tissue engineering, flexible electronic devices, antibacterial composites, photovoltaic devices, and physical sensors. Its excellent properties can be used to develop smart nanomaterials with enhanced properties for various advanced applications. There is no doubt that graphene-based nanomaterials are helping to develop next generation technologies with enhancing properties to change people's lifestyles. This book provides an overview of recent research and development of synthesis of graphene and its applications.